The Agglomeration of Food Services and Their Colocation with Surrounding Complementary Services in the Guangdong–Hong Kong–Macao Greater Bay Area - Wang, Yixiao; Wu, Xibo; Qin, Jian; Zhang, Xiaoying; Wang, Xiangyu (ISPRS international journal of geo-information, 2025)
This study explores the spatial distribution of food services and their colocation with surrounding complementary services. It investigates these issues within the Guangdong–Hong Kong–Macao Greater Bay Area (GBA), utilizing point-of-interest (POI) data, spatial kernel density, the HDBSCAN clustering algorithm, and colocation quotients. The findings are as follows: (1) this research reveals a significant spatial agglomeration of food services near the Pearl River, with notable food clusters across administrative boundaries; (2) Guangzhou, Shenzhen, Foshan, and Dongguan provide a significant quantity of food services, while Hong Kong and Macao feature the highest percentages of foreign cuisine; (3) the colocation between food services and surrounding services is concentrated along the Pearl River; (4) leisure, education, and residential services are key factors attracting the proximity of food services; (5) leisure, education, retail, and tourism services exhibit the strongest attractiveness to Chinese food, while residential and healthcare services are closely linked to the distribution of snacks, and transportation services attract snacks and beverages.